Assessment of simple risk markers for early mortality among HIV-infected patients in Guinea-Bissau: a cohort study. Issue 6 (14th November 2012) - Oliveira, Inés; Andersen, Andreas; Furtado, Alcino; Medina, Candida; da Silva, David; da Silva, Zacarias J; Aaby, Peter; Laursen, Alex Lund; Wejse, Christian; Eugen-Olsen, Jesper; ,
Abstract : Background: Decisions about when to start an antiretroviral therapy (ART) are normally based on CD4 cell counts and viral load (VL). However, these measurements require equipment beyond the capacity of most laboratories in low-income and middle-income settings. Thus, there is an urgent need to identify and test simple markers to guide the optimal time for starting and for monitoring the effect of ART in developing countries. Objectives: (1) To evaluate anthropometric measurements and measurement of plasma-soluble form of the urokinase plasminogen activator receptor (suPAR) levels as potential risk factors for early mortality among HIV-infected patients; (2) to assess whether these markers could help identify patients to whom ART should be prioritised and (3) to determine if these markers may add information to CD4 cell count when VL is not available. Design: An observational study. Setting: The largest ART centre in Bissau, Guinea-Bissau. Participants: 1083 ART-naïve HIV-infected patients. Outcome measures: Associations between baseline anthropometric measurements, CD4 cell counts, plasma suPAR levels and survival were examined using Cox proportional hazards models. Results: Low body mass index (BMI≤18.5 kg/m 2 ), low mid-upper-arm-circumference (MUAC≤250 mm), low CD4 cell count (≤350 cells/μl) and high suPAR plasma levels (>5.3 ng/ml) were independent predictors of death. Furthermore, mortality among patients with low CD4 cell count, low MUAC or low BMI was concentrated in the highest suPAR quartile. Conclusions: Irrespective of ART initiation and baseline CD4 count, MUAC and suPAR plasma levels were independent predictors of early mortality in this urban cohort. These markers could be useful in identifying patients at the highest risk of short-term mortality and may aid triage for ART when CD4 cell count is not available or when there is shortness of antiretroviral drugs.